Methods of detection and typing of methicillin resistant Staphylococcus aureus isolated from animals - Radosavljević V.; Žutić Jadranka; Pavlović Ljiljana; Bošković Tamara; Radanović O.; Žutić M. (Veterinarski Glasnik, 2014)
In this work there was evaluated the method of detection of methicillin resistant Staphylococcus aureus (MRSA) by using two molecular and three phenotypic tests in investigation procedure of 70 strains of S.aureus isolated from animals. Recent findings of the new mecA homologue, mecALGA251, minimise the significance of mecA gene presence detection as a confirmation method of methicillin resistant Staphylococcus aureus identification. For this reason, along with multiplex PCR set of primers(165rDNK, nuc, mecA) for detection mecA gene, there was also used multiplex PCR set of primers (spa, mecA, pvl, mecALGA251) for differentiation mecALGA251 from mecA, with simultaneous detection of luk-PV and spa gene fragments. In all 70 investigated isolates there was detected the presence of specific 16 SrDNK fragment and nuc gene which encodes a thermostable S. aureus nuclease, while in 5 out of 70 S. aureus isolates, there was proven mecA gene presence using two multiplex PCR tests. In the investigated strains there was determined neither mecC (mecALGA251)gene presence, nor Panton Valentine Leukocidin encoding gene. By application cefoxitin disk-diffusion, latex-agglutination and two multiplex PCR tests, the identical results in identification 5 methicillin resistant out of 70 investigated S. aureus strains were obtained. In our investigation there was determined a complete correlation between the results of phenotypic and genotypic identification of methicillin resistant S. aureus. [Projekat Ministarstva nauke Republike Srbije, br. TR 31079]